1986
DOI: 10.1021/jf00070a029
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of fenitrothion and fenitrooxon by the fungus Trichoderma viride

Abstract: The fungus Trichoderma viride Persoon was found to effect the hydrolysis of fenitrothion (Sumithion) and fenitrooxon in pure culture. After incubation with the test compounds, liquid cultures were extracted with ethyl acetate and the extracts were analyzed by gas chromatography for residual test compounds and their hydrolysis product, 3-methyl-4-nitrophenol. A cleanup procedure, using Amberlyst A21 resin, was developed to facilitate the analysis. Evidence was found to suggest that this nitrophenol is cometab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 6 publications
1
16
1
Order By: Relevance
“…Studies of the biodegradation of organophosphorus insecticides by fungi include degradation of fenitrothion by Trichoderma viride, Mortierella isabellina and Saprolegnia parasitica (Baarschers and Heitland 1986) and chlorpyrifos, fonofos and terbufos by Phanerochaete chrysosporium (Bumpus et al 1993). However, the present study appears to be the first to report the integration and expression of a versatile bacterial degradation gene in fungi.…”
Section: Discussionmentioning
confidence: 75%
“…Studies of the biodegradation of organophosphorus insecticides by fungi include degradation of fenitrothion by Trichoderma viride, Mortierella isabellina and Saprolegnia parasitica (Baarschers and Heitland 1986) and chlorpyrifos, fonofos and terbufos by Phanerochaete chrysosporium (Bumpus et al 1993). However, the present study appears to be the first to report the integration and expression of a versatile bacterial degradation gene in fungi.…”
Section: Discussionmentioning
confidence: 75%
“…Many studies concern pesticide degradation by Trichoderma spp., but the majority of them are conducted in culture media in laboratory conditions propitious for fungal growth. T. viride can degrade several organophosphorus (fenitrothion, fenitrooxon, parathion methyl), carbamate, and chlorinated hydrocarbon insecticides: DDT, endrin, aldrin [12,14,17,40]. In studies conducted by Katayama and Matsumura [13], T. harzianum, was found to degrade DDT, dieldrin, endosulfan, pentachloronitrobenzene, and pentachlorophenol, but not hexachlorocyclohexane.…”
Section: Discussionmentioning
confidence: 99%
“…[24]Aspergillus niger JQ660373 [25], extracellular fungal hydrolases [26] has been proved efficient for the degradation of MCP. In addition to this other organophosphorus (OP) pesticides such as fenitrothion [phosphorothioic acid O,O-dimethyl-O-(3methyl-4-nitrophenyl) ester] has also been, known to be degraded by Trichoderma viride, MortierelIa isabeIIina, and Saprolegnia parasitica [27]. Bumpus et al, [28]had reported that P. chryososporium is able to degrade chlorpyrifos, fonofos, and terbufos to carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%